User Acceptance of Assistive Electric Motorcycles for Physical Disabilities: An Analysis of the Technology Acceptance Model in the Context of Special Education - Asrorul Mais; Lailil Aflahkul Yaum (Journal La Edusci, 2026)
This study aims to analyze user acceptance of assistive electric reverse trike motorcycles for individuals with physical disabilities within the context of Special Education in Higher Education using the Technology Acceptance Model (TAM) approach. This research employed a descriptive qualitative method with interview and observation techniques involving 16 informants consisting of users, lecturers, technicians, and members of the disability community. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that perceived usefulness and perceived ease of use have a positive influence on attitudes toward use and the actual use of the assistive motorcycle. This vehicle is proven to enhance campus accessibility, learning independence, and academic participation of students with physical disabilities. However, acceptance is also influenced by external factors such as family support, university policies, and infrastructure. This study confirms that assistive mobility technology plays a crucial role in realizing inclusive higher education